2014
DOI: 10.1007/s00216-014-8085-0
|View full text |Cite
|
Sign up to set email alerts
|

Stability-indicating RP-LC method for determination of azilsartan medoxomil and chlorthalidone in pharmaceutical dosage forms: application to degradation kinetics

Abstract: A RP-LC method was developed and validated for simultaneous determination of the active components, azilsartan medoxomil (AZL) and chlorthalidone (CLT), in their novel antihypertensive combined recipe. The chromatographic separation was achieved on an Eclipse XDB-C18 (4.6 × 150 mm, 5 μm) column using a mobile phase consisting of methanol/potassium hydrogen phosphate buffer (pH 8, 0.05 M) (40:60, v/v) in isocratic mode. The flow rate was maintained at 0.8 mL min(-1) at ambient temperature. Detection was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…88 Many drugs degrade through ethereal cleavage even in mild acidic medium at different temperatures. Ambrisentan, 89 azilsartan, 32 Figure 2). Baertschi and Alsante have very clearly outlined the pathway of degradation of duloxetine due to cleavage of ether linkage, 96 which is supported by Bansal et al to explain the similar degradation behaviour of toremifene.…”
Section: Conventional Hydrolytic Reactionsmentioning
confidence: 99%
“…88 Many drugs degrade through ethereal cleavage even in mild acidic medium at different temperatures. Ambrisentan, 89 azilsartan, 32 Figure 2). Baertschi and Alsante have very clearly outlined the pathway of degradation of duloxetine due to cleavage of ether linkage, 96 which is supported by Bansal et al to explain the similar degradation behaviour of toremifene.…”
Section: Conventional Hydrolytic Reactionsmentioning
confidence: 99%
“…Different analytical methods for the determination of chlorthalidone impurities have been reported. e reported methods describe degradation studies and the estimation of assay and impurity profiles for both drug substance and drug product, as well as in combination with other drug substances [18][19][20][21][22][23]. e proposed analytical method can be performed effectively on chlorthalidone API and chlorthalidone tablets for known EPspecified, process-related, and degradation impurities.…”
Section: Introductionmentioning
confidence: 99%
“…AZM was approved by the food and drug administration (FDA) in 2011 and available as 80 mg and 40 mg tablets. The literature review on availability of analytical methods for AZM revealed an UV spectroscopic method, 4 stability indicating high performance thin layer chromatographic (HPTLC) method, 5 few liquid chromatographic (LC) methods [6][7][8][9][10][11] and LC-MS methods 12,13 for the quanti fication of AZM in bulk drug, plasma and in combination with other drugs. There are two reports on the estimation of azilsartan medoximil by HPLC viz.…”
Section: Introductionmentioning
confidence: 99%